Multigene phylogeny and Taxonomy of Cephalotrichum telluricum: A Coprophilous Fungus in Northern Thailand - Balagamage, D.t.; Maharachchikumbura, S.s.n.; Phukhamsakda, C.; Liu, Jian-Kui; Hyde, Kevin D.; Al-Otibi, Fatimah (Phytotaxa, 2026)
Cephalotrichum (Microascaceae) is a diverse genus with 72 currently recognized species found worldwide. It is characterized by the formation of dry-spores, indeterminate synnemata and enteroblastic percurrent conidiogenesis. Species of Cephalotrichum are endophytes, saprobes, and opportunistic pathogens in animals or humans. A strain of Cephalotrichum telluricum was isolated from the dung of a Guinea pig in Thailand. Maximum likelihood and Bayesian inference analysis of the combined internal transcribed spacer (ITS), large-subunit rDNA (LSU), elongation factor-1 alpha (tef1-α) and beta tubulin (tub2) sequence data revealed that the new isolate clustered with the ex-type of C. telluricum. Based on morphological and multigene phylogenetic evidence, we introduce the new strain as C. telluricum (MFLUCC 25-0237), report a novel host and geographical record from Guinea Pig dung, in northern Thailand.